Thermodynamic description of the C-Ge and C-Mg systems - Hu B.; Du Y.; Xu H.; Sun W.; Zhang W.W.; Zhao D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The thermodynamic modeling for the C-Ge and C-Mg systems is performed by the CALPHAD method. The enthalpy of formation for Mg2C3, the experimental value of which is not available in the literature, is obtained via first-principles calculation to refine the thermodynamic modeling of the C-Mg system. A comparison of the thermodynamic calculations with the available literature data shows that the presently obtained two sets of thermodynamic parameters for the C-Ge and C-Mg systems can well describe the these two systems.